Quantification of Escherichia Coli Bacteria in Municipal Wastewater Treatment Plant and Their Degradation Using Advanced Oxidation Processes - Simiyu, Robin (UoEm, 2025)
Pathogenic microorganisms in wastewater present a major global public health concern, underscoring the critical necessity for effective wastewater treatment and advanced distribution infrastructure. While chlorination remains a common disinfection method, it presents notable drawbacks, including the necessity for high dosages and the potential formation of toxic trihalomethanes, which are detrimental to human health. This research sought to assess the efficacy of advanced oxidation processes (AOPs) for disinfecting municipal wastewater obtained from the Embu sewage treatment plant. AOPs are chemical oxidation methods that generate highly reactive oxygen species (ROS), such as hydroxyl radicals, which rapidly disinfect water by attacking impurities. The study investigated individual AOP systems, specifically UV photolysis and H2O2 disinfection, alongside various hybrid AOP configurations: UV/H2O2, UV/TiO2, and UV/TiO2/H2O2. The findings indicated that UV photolysis alone achieved 81% E. coli removal, while H2O2 disinfection yielded an 86% efficiency. However, it was observed that excessive H2O2 concentrations could scavenge the generated hydroxyl radicals, thereby impeding E. coli inactivation. Significantly, the UV/H2O2, UV/TiO2, and UV/TiO2/H2O2 hybrid systems consistently demonstrated higher disinfection percentages compared to their singleprocess counterparts. The UV/H2O2 system achieved 89% E. coli removal within 60 minutes using a 1.4 mM H2O2 concentration. The UV/TiO2 system showed a slightly greater inactivation rate, reaching 91%. The UV/TiO2/H2O2 hybrid system proved most effective, achieving 100% E. coli inactivation within 50 minutes. This inactivation grew due to the combined effect that was caused by hydroxyl radical formation when UV, H2O2, and TiO2 were applied collectively. The successful destruction of E. coli was also facilitated by the application of zeolite, a highly effective adsorbent whose surface area was 22.44 m²/g and therefore enhanced immensely the adsorption process. There was also no reactivation of E. coli observed after being treated, confirming for certain the complete destruction of bacterial cells. This was also confirmed by protein analysis, whose result showed protein content reduction in treated solutions. Catalyst characterization also showed that the used TiO2 had 95.6% anatase phase. Based on these findings, it is recommended that hybrid UV/H2O2/TiO2 be applied for disinfection at the Embu wastewater treatment plant to prevent discharging poorly treated wastewater to the environment. In this study, the zeolite used was clinoptilolite, which acted as both an adsorbent and a support for TiO₂. The photocatalyst applied in hybrid systems was therefore TiO₂–clinoptilolite, not TiO₂ alone, and this composite material enhanced both adsorption and photocatalytic activity during disinfection.
Masters Thesis